Development Prospects of Software Defined Optical Networks - Yuefeng Ji; Jie Zhang; Yongli Zhao (Dianxin kexue)
In order to meet the requirement of continued growth in broadband services and applications, optical networks need to be more and more flexible and controllable. Software defined optical network（SDON）focuses on an integrated optical networking solution based on software defined technology, and the key technologies are related to software-defined optical transmission, switching and networking, etc. Based on the analysis of technological characteristics of SDON, the necessity and feasibility of introducing SDON were discussed, and several application scenarios of SDON were proposed. All these show that SDON will play an important role in the development process of next-generation intelligent optical networks forwards to high efficiency, flexible scheduling, and virtual reconstruction.